KAJIAN PENERAPAN GAYA ARSITEKTUR MUGHAL PADA ELEMEN FASAD MASJID AGUNG TENGKU KHALILULLAH - Mira Alfitri; Muhammad Rosil; Zia Faizurrahmany El Faridy (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
This study explores the application of Mughal architectural concepts to the facade of the Tengku Khalilullah Grand Mosque in Simeulue Regency. This mosque is an icon of Simeulue Regency, built with architectural elements influenced by Mughal culture, such as large domes, symmetrical gardens, decorative gates, and distinctive ornaments. With a qualitative approach, this study used observation and interview methods to collect primary and secondary data on the characteristics of the mosque's design.